Can Corporate Social Responsibility Influence Debt Financing for Companies on the Indonesian Stock Exchange - Selly; Serly (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - The research aims to evaluate the consequences of Corporate Social Responsibility (CSR) related to debt financing in companies listed on the Indonesia Stock Exchange (BEI) in the period 2017 to 2021. The variables that are the subject of the study include: debt financing, Corporate Social Responsibility (CSR) , Sales Growth, Tobin's Q, return on assets (ROA). Research Method - The research sample consisted of 300 data obtained from 60 companies that had published sustainability reports and financial reports for the period 2017 to 2021 which were selected through purposive sampling. The panel regression analysis method was used as an examination tool in this research. CSR measurement uses environmental, social and governance disclosure scores obtained from data. Debt financing is measured as long-term debt to total assets. Sales Growth is measured as the percentage of marketing growth from year n-1 to year n. Return On Assets is measured as a ratio. Tobin's q is measured by combining the market value of equity and total liabilities relative to total assets. Findings - Empirical results show that the CSR variable does not have an essential negative impact on debt financing in companies listed on the IDX. Implication - The implication of this research is that CSR regarding debt financing can affect companies listed on the Indonesian Stock Exchange so that debt financing figures must be minimized both financially and in financial reports for the company so that sales growth will increase and the company will not experience losses.